2022
DOI: 10.1017/pab.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Fossilized pollen malformations as indicators of past environmental stress and meiotic disruption: insights from modern conifers

Abstract: Pollen malformations have been proposed as a paleoenvironmental stress proxy. However, the frequency and variability of pollen malformations under near-optimal conditions and environmental stress, as well as their developmental origins, remain unclear. To bridge these gaps, we compared pollen malformation frequencies and assemblages of 14 extant conifer genera of Pinaceae and Podocarpaceae producing saccate (winged) grains grown under near-optimal conditions. These baseline pollen yields were compared with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 96 publications
0
11
0
Order By: Relevance
“…This peculiar characteristic, though, could be the result of a taphonomic artefact rather than environmental stress; therefore, further studies are needed to validate this external trait. The few occurrences of spore dyads and tetrads were less than 1% on average and, therefore, below the baseline frequency of 3-5% above which environmental influence on spore and pollen morphology can be assumed 1,8,12,63 . They reflect the natural variation of spore and pollen morphology (e.g., 64,65 ).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…This peculiar characteristic, though, could be the result of a taphonomic artefact rather than environmental stress; therefore, further studies are needed to validate this external trait. The few occurrences of spore dyads and tetrads were less than 1% on average and, therefore, below the baseline frequency of 3-5% above which environmental influence on spore and pollen morphology can be assumed 1,8,12,63 . They reflect the natural variation of spore and pollen morphology (e.g., 64,65 ).…”
Section: Resultsmentioning
confidence: 75%
“…Teratology is the science of malformation that occurs during the development of an organism. Spores and pollen are also known to show teratomorph morphologies, sometimes in frequencies exceeding the background values of plants grown under present-day natural conditions 1 . In palaeopalynology, teratomorphic spores and pollen have been successfully employed as a proxy for increased environmental disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Land vegetation can provide insights into ecosystem health in the fossil record. In particular, plants can uniquely indicate paleoenvironmental stresses by leaving behind structural malformations in their spores and/or pollen under conditions such as heightened radiation and chemical pollutant exposure (Visscher et al, 2004;Foster & Afonin, 2005;Bazhina et al, 2007;De Storme & Geelen, 2013;Benca et al, 2018Benca et al, , 2022Lindström et al, 2019;Looy et al, 2021). Several studies have shown that volcanism is a key factor for long-term climate change, and global warming is widely regarded to have played a contributing role in numerous past biotic crises (Sun et al, 2012;Payne & Egan, 2019;Chen & Xu, 2019).…”
mentioning
confidence: 99%
“…Phytotoxic volcanic emissions and radiation stress can cause abnormalities in plants and malformed spores and pollen (sporomorphs), and tetrad formation (Mičieta & Murin, 1996;Visscher et al, 2004Visscher et al, , 2011Foster & Afonin, 2005;Yin et al, 2014;Hochuli et al, 2017;Benca et al, 2018Benca et al, , 2022Benton, 2018;Lindstrӧm et al, 2019;Grasby et al, 2020;. Numerous malformations have been shown to associate with environmental stress, but some types of morphological alterations are not suitable for environmental stress detection as they do not require stress to form, such as normally unseparated spore tetrads in some arid land lycophytes, unseparated tetrads of Classopollis pollen, or the pollen of the rare plant species that naturally produce trisaccate grains.…”
mentioning
confidence: 99%
See 1 more Smart Citation